Isofraxidin inhibits the proliferation and differentiation of the osteoblast MC3T3-E1 subclone 14 cell line: Efficacy of isofraxidin in ankylosing spondylitis - Xu, Junliang; Ji, Wei (Cellular and Molecular Biology, 2023)
Ankylosing spondylitis (AS) is an autoimmune inflammatory disease associated with joint inflammation and destruction. Current treatment modalities alleviate symptoms; however, they cannot cure the disease and are associated with significant side effects. Thus, we aimed to confirm the inhibitory effect of isofraxidin, a herbal extract, on pathological osteogenesis in ankylosing spondylitis to better treat patients affected by the disease. Mouse preosteoblast MC3T3-E1 subclone 14 cells were used in vitro to establish control and isofraxidin intervention groups. Cell viability was then determined using the MTT assay; the expression of osteogenic factors, including Runx2, OSX, collagen I, and ALP was measured using qRT-PCR and western blotting. Final osteogenic mineralization was performed by alizarin red staining. The results showed that isofraxidin could inhibit osteoblast viability; however, this effect was nullified at concentrations of 0-20 µM after adding 1% serum. Gene and protein expression of the osteogenic factors RUNX2, OSX, Collagen I, and ALP was inhibited, and a similar trend was exhibited at 7, 14, and 21 days after isofraxidin treatment. This trend was further verified by alizarin red staining of the final osteogenic mineralized nodules on days 7, 14, 21, and 35. Isofraxidin inhibits MC3T3-E1 subclone 14 proliferation and differentiation and may be considered a potential drug therapy for treating pathological osteogenesis in ankylosing spondylitis.